Pengaruh Jenis Limbah Aluminium Pada Proses Pengecoran Menggunakan Tungku Krusibel Terhadap Nilai Kekerasannya - David Dwi Putra; Faisal Haqqoni; Mohammad Nurhilal; Ulikaryani Ulikaryani (Infotekmesin, 2023)
Aluminum waste that has accumulated due to the widespread use of aluminum in household needs, daily life, and in the manufacture of industrial material components will have an impact on the environment if not handled properly. It is necessary to utilize aluminum waste in a product that has a sale value through a casting process using a crucible furnace. This research was conducted to determine the hardness differences of waste aluminum from used aluminum cans, used aluminum pots, and used aluminum wires melted in a smelting furnace. This study uses quantitative analysis and experimental research types. Tests carried out on this crucible furnace were carried out to determine the effect of the type of aluminum waste and the length of time it took to smelt the three types of material on the hardness results. The results of the Rockwell hardness test on aluminum can waste have an average value of 71.38 HRB, on aluminum pans waste it has an average value of 71.68 HRB, and on aluminum cable waste it has an average value of 53.02 HRB.